2017
DOI: 10.1073/pnas.1620811114
|View full text |Cite
|
Sign up to set email alerts
|

Historical climate controls soil respiration responses to current soil moisture

Abstract: Ecosystem carbon losses from soil microbial respiration are a key component of global carbon cycling, resulting in the transfer of 40–70 Pg carbon from soil to the atmosphere each year. Because these microbial processes can feed back to climate change, understanding respiration responses to environmental factors is necessary for improved projections. We focus on respiration responses to soil moisture, which remain unresolved in ecosystem models. A common assumption of large-scale models is that soil microorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 33 publications
11
133
3
Order By: Relevance
“…We suggest that microbial communities in sediments that are inundated permanently or for extended periods are better adapted to full water saturation than those that are infrequently inundated, which led to the binary RR response between 0-day sediments and the other inundation histories. This finding is similar to that of Hawkes et al (2017), who reported that historically wetter soil emitted twice as much carbon, on average, than historically drier soils.…”
Section: Microbial Respiration Response To Inundationsupporting
confidence: 89%
See 1 more Smart Citation
“…We suggest that microbial communities in sediments that are inundated permanently or for extended periods are better adapted to full water saturation than those that are infrequently inundated, which led to the binary RR response between 0-day sediments and the other inundation histories. This finding is similar to that of Hawkes et al (2017), who reported that historically wetter soil emitted twice as much carbon, on average, than historically drier soils.…”
Section: Microbial Respiration Response To Inundationsupporting
confidence: 89%
“…In the Hanford Reach of the Columbia River, for example, hydropower dam operations cause river water elevation to fluctuate up to 2 m in a single day (Arntzen et al, 2006). Over time, cycles of wetting and drying impact different elevations of the parafluvial zone at different frequencies, which not only naturally results in a gradient of sediment moisture content but also has the potential to create biogeochemical and microbial interactions specifically dependent on preceding environmental conditions (Hupp and Osterkamp, 1996;Larned et al, 2010;Tockner et al, 2000;Hawkes et al, 2017). Given that dam-impacted parafluvial zones are globally ubiquitous and likely to expand with ongoing dam construction efforts, there is a need to identify the processes impacted by the history of variable inundation.…”
Section: Introductionmentioning
confidence: 99%
“…The soils are generally not appropriate for small grain or row crop production due to high erosion rates, shallow depths, and low water retention capacity (Woodruff and Wilding, 2008) but are well suited for grazing and viticulture. Mean annual precipitation ranges from 887 mm in the east to 442 mm in the west on the plateau, decreasing by about 10 cm every 100 km (Hawkes et al, 2017). At TxSON, the 30‐yr mean annual precipitation normal is 807 mm and air temperature is 18.4°C (PRISM Climate Group, Oregon State University, http://prism.oregonstate.edu/, accessed 14 Dec. 2018).…”
Section: Study Areamentioning
confidence: 99%
“…To the best of our knowledge, the legacy effects of drought on soil biogeochemical processes and the microbial community after fire have not been investigated to date. Long‐term legacies were found in a number of sites across the world when comparing past and current climates (Averill, Waring, & Hawkes, ; Delgado‐Baquerizo et al, ; Hawkes, Waring, Rocca, & Kivlin, ). The legacy effects of changes in climate, including drought, on soil remain a topic of research.…”
Section: Introductionmentioning
confidence: 99%